Customer Experience, Kepuasan Wisatawan dan Loyalitas Wisatawan di Floating Market Lembang Bandung - Hibatullah, Naufal; Suardana, I Wayan; Sudiarta, I Nyoman (Jurnal Master Pariwisata (JUMPA), 2022)
Problems that arise in the Lembang Floating Market with the presence of new competitors for man made tourist destinations in the city of Bandung which have caused a decrease in tourist visits to Lembang Floating Market and also the inability of the Lembang Floating Market to provide a positive experience for tourists who come who are dissatisfied. Therefore, this study aims to 1) explain the influence of customer experience on tourist satisfaction at the Lembang Floating Market, 2) the influence of tourist satisfaction on their loyalty to the Lembang Floating Market, 3) the influence of customer experience on tourist loyalty at the Lembang Floating Market, 4) to explain the influence of customer experience on tourist loyalty through tourist satisfaction. The sample in this study was 100 respondents from domestic tourists. Determining respondents based on accidental sampling and the data analysis method used is a quantitative approach in the form of a structural equation model (SEM) with the SmartPLS version 3.0 analysis tool which is measured using a Likert scale. The results of this study indicate that a) customer experience has a positive and significant effect on tourist satisfaction, b) tourist satisfaction has a positive and significant effect on tourist loyalty, c) customer experience has a positive and significant effect on tourist loyalty at Floating Market Lembang Bandung, d) customers experience has a positive and significant effect on tourist loyalty through tourist satisfaction. Suggestions for the manager of the Lembang Floating Market is to maintain and improve the customer experience obtained by visiting tourists because this strategy will have a positive effect on tourist satisfaction and loyalty in the future. Keywords: Customer Experience, Tourist Satisfaction, Satisfaction, Tourist Loyalty.